Analysis of Temperature, Pressure and Soot Density on a Single Cylinder Diesel Engine - Mohd Hafidzal, M.H.; Mohamad Isa, N.N.; Roslizar, A; Akop, M.Z.; Zakaria, M.S.; Ridhwan, J. (Journal of Engineering and Technology (JET), 2014)
In order to develop and improves the efficiency of the diesel engine, various of works and researches had been done. The most commonly research studies are internal combustion engine and the emmisions. This study focused on temperature, pressure and soot in a single cylinder diesel engine. Studies using experimental methods require a lot of cost, manpower, time and high technology equipment. Therefore, the simulation such as Computational Fluid Dynamic (CFD) can be used to conduct a study on the model engine by entering a few geometry settings and types of simulations to be performed. By using CFD FLUENT simulations, this study aims to investigate the distribution of temperature, pressure and soot formation in diesel internal combustion engine. In this study, CFD simulations were conducted on an internal combustion diesel engine model in 2D by using the eddy- dissipation model and non-premixed combustion. All engine parameters and dimensions have been taken from the actual engine model-KM186 KIPOR diesel engine. Results of simulations conducted have found that the maximum pressure obtained was 71.78MPa pressure with a temperature derived at 918K. Both the pressure and maximum temperature obtained from the crank angle of 720° (+0° ATDC). Soot formation is increased dramatically immediately after igniting fuel into the combustion chamber. During combustion, the average value soot density is 0.023284 kg/m3 at 732° (+12° ATDC).